First principles and experimental studies of empty Si46 as anode materials for Li-ion batteries. Issue 23 (17th November 2016) - Chan, Kwai S.; Miller, Michael A.; Liang, Wuwei; Ellis-Terrell, Carol; Chan, Candace K.
Abstract: Abstract : The objective of this investigation was to utilize the first-principles molecular dynamics computational approach to investigate the lithiation characteristics of empty silicon clathrates (Si46 ) for applications as potential anode materials in lithium-ion batteries. The energy of formation, volume expansion, and theoretical capacity were computed for empty silicon clathrates as a function of Li. The theoretical results were compared against experimental data of long-term cyclic tests performed on half-cells using electrodes fabricated from Si46 prepared using a Hofmann-type elimination–oxidation reaction. The comparison revealed that the theoretically predicted capacity (of 791.6 mAh/g) agreed with experimental data (809 mAh/g) that occurred after insertion of 48 Li atoms. The calculations showed that overlithiation beyond 66 Li atoms can cause large volume expansion with a volume strain as high as 120%, which may correlate to experimental observations of decreasing capacities from the maximum at 1030 mAh/g to 553 mA h/g during long-term cycling tests. The finding suggests that overlithiation beyond 66 Li atoms may have caused damage to the cage structure and led to lower reversible capacities.